2018
DOI: 10.1016/j.amsu.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of bilateral ovarian dysgerminoma with 11-year follow-up: A case report

Abstract: IntroductionMalignant ovarian germ cell tumors (MOGCTs) are rare malignancies with an incidence of about 0.5/100,000. They account for less than 5% of all ovarian tumors, of which 32.8% are dysgerminomas, the female analogue of seminomas. These tumors occur in all age groups, with peak incidence below the age of 20 years in women.AimTo describe the case of a bilateral ovarian dysgerminoma treatment with 11-year follow-up.MethodsCase report with details regarding clinical history, surgical treatment, chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
5

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
1
10
0
5
Order By: Relevance
“…22 In another study, the most common type of MGCT was dysgerminoma (38.2%) followed by yolk sac tumor (30.4%), and immature teratoma comprised of (15.7%). 23 where as in this study yolk sac tumor was found to be the most common type of MGCT.…”
Section: Discussionsupporting
confidence: 61%
“…22 In another study, the most common type of MGCT was dysgerminoma (38.2%) followed by yolk sac tumor (30.4%), and immature teratoma comprised of (15.7%). 23 where as in this study yolk sac tumor was found to be the most common type of MGCT.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, we do not agree when a patient is affected by a bilateral ovarian disease, we try to perform a sparing fertility surgery, Zogby and coworkers do not preserve ovary and uterine corp, and the uterus and just partial contralateral ovary were affected by the tumor. 19,20 Always we propose to preserve the reproductive and endocrinal function.…”
Section: Discussionmentioning
confidence: 99%
“…Letztlich waren es also die schwangerschaftsbedingten Veränderungen, die in unserem Fall dafür verantwortlich waren, dass bei Erstdiagnose bereits primär ein Stadium FIGO IIIC vorlag, obwohl das Dysgerminom in der Literatur zu den Tumorentitäten zählt, die aufgrund ihres schnellen Wachstums bereits in Frühstadien diagnostiziert werden können: In ca. 75 % der Fälle liegt bei Erstdiagnose ein Stadium FIGO I vor [5,7,8,19]. Operationen in der Schwangerschaft gelten mittlerweile als relativ sichere Eingriffe, sofern sie an Zentren mit entsprechender Expertise durchgeführt werden [21,22].…”
Section: Eingeschränkte Untersuchungsmöglichkeiten In Der Schwangerscunclassified
“…Bis auf das reife Teratom gelten alle Keimzelltumoren als maligne und zeichnen sich durch ein schnelles Wachstum aus [5]. Das Dysgerminom ist mit einem Anteil von etwa 33 % der häufigste maligne Keimzelltumor, mit einer Inzidenz von 0,2-1/100 000 aber trotzdem ein sehr seltenes Malignom [5,8]. Ein Auftreten in der Schwangerschaft ist wegen seines Altersgipfels möglich, stellt aber eine ausgesprochene Seltenheit dar [3,5].…”
Section: Introductionunclassified
See 1 more Smart Citation